Respectful Maternity Care (RMC) from Perspectives of Pregnant Women and Midwives in Independent Midwifery Practices (IMPs) - Rika Agustina; Komalasari Komalasari; Yunita Rahma; Juntika Nurikhsan (Indonesian Journal of Global Health Research, 2026)
RMC and abuse in the delivery room are associated with negative experiences in childbirth and a poor maternal care quality index. Despite many advances in maternal and child health, there are still maternal and infant mortality rates worldwide. SDGs aim to reduce MMR to less than 70 per 100,000 live births by 2030. In Indonesia, the MMR data per 100,000 live births in January 2023 were around 305. This figure ranks Indonesia second in terms of the highest MMR cases in ASEAN. Objective: To explore childbirth readiness in third-trimester pregnant women and to explore the RMC provided by health workers during services. Method: This research design employs a qualitative approach, with 20 pregnant women participating in the focus group discussion (FGD) method and 6 midwives participating in in-depth interviews. The sampling technique is stratified random sampling of 6 midwife areas representing the Pringsewu area. Results: 10 themes and 35 sub-themes were obtained from the midwife's perspective, and 8 themes and 24 sub-themes from the pregnant woman's perspective. Data obtained from quantitative data with questionnaires and qualitative with interviews, indepth interview. RMC from the midwife's perspective are the midwife's authority, documentation, informed consent, referral, midwife's competence, service quality, midwife's experience, care needs, and midwife's responsibility. RMC from the pregnant woman's perspectives includes care according to needs, fairness and no discrimination, the right to information, confidentiality and privacy, protection from physical injury, dignity and respect, not being neglected.